Valuing an ecotourism resource : a case study of the Boulders Beach African penguin colony - Lewis, Sarah E F (Department of Biological Sciences, 2014)
The colony of African Penguins at Boulders, Simon's Town on the southern Cape Peninsula, Western Cape formed in 1985, and is now a major ecotourism destination. The African Penguin is listed as Endangered due in part to competition with commercial fisheries. Improvements in the spatial management of these fisheries could assist with the conservation of the penguins, but would be costly. Various techniques were used to estimate the value of the colony, and to assess its impact on the economy of the southern Peninsula.